Employing two types of feedback and two styles of learning in a ubiquitous learning environment for developing technological skills and technology acceptance among educational technology students - Zeinab El_Agizy (International Journal of Advanced Humanities Research)
The aim of the present study is to investigate the effectiveness of using feedback (corrective/explanatory) and the learning style (individual/cooperative) in a ubiquitous learning environment to develop some technological skills such as designing educational websites and technological acceptance among technology students. For this goal, the researcher prepared tools of the study: (1) a list of criteria for designing a ubiquitous learning environment, (2) an achievement test and an observation card for designing electronic websites, (3) a scale for technological acceptance, and (4) the design of a ubiquitous learning environment. The tools of the study were pre and post applied on the research sample, which consisted of (60) male and female students from the Department of Educational Technology at the Faculty of Specific Education, Tanta University. The sample was divided into four groups: each group (15) male and female students, according to the type of feedback and learning style. The research has concluded that there are statistically significant differences in favor of the experimental group that received explanatory feedback and the cooperative learning style over the other experimental groups. Moreover, the study recommended the necessity of using explanatory feedback and collaborative learning environment to develop the skills of designing educational website and technological acceptance among educational technology students